POLA BERDEMOKRASI DALAM UUD 1945 SESUDAH AMANDEMEN - Siti Hasanah (Media Keadilan: Jurnal Ilmu Hukum, 2022)
The fourth precept of Pancasila is the spirit of democracy with Indonesian characteristics. There are differences in the pattern of democracy in the state constitution before and after the amendment of the 1945 Constitution. The spirit of democracy in the provisions of the 1945 Constitution (before the amendment), Article 1 paragraph (2) is purely characterized by Pancasila Democracy which boils down to a communal base characterized by deliberation and representation. After the amendment of the 1945 Constitution the pattern changed both at the substantive and implementation levels. Substantively, the spirit of democracy contained in the provisions of Article 22E paragraph (2) of the 1945 Constitution (after the amendment) shifted to the principle of Liberal democracy which boils down to an invidual basis reflected in the system of direct elections and decision-making with a majority of votes. The method used in this paper is normative juridical with a focus on approaches using conceptual approaches, statute approaches, historical approaches. The purpose of the study was to see the differences in the substance and implementation of democratic patterns in the 1945 Constitution before and after the amendment of the 1945 Constitution.